Three Brazilian species of Begonia (Begoniaceae) from the state of Rio de Janeiro, Brazil - Jacques, Eliane De Lima (Phytotaxa, 2022)
Begonia altimontana, B. inumbrata and B. pedrabrancencis (Begoniaceae) are species endemic to the Brazilian Atlantic Coastal Forest, an area rich in endemism and species diversity, and are described and illustrated herein. Begonia altimontana resembles B. olsoniae L.B.Sm. & B.G.Schub., B. princeps A.DC. and B. ramentacea Paxton in the shape of leaf blades and squamulose petioles, and is found in the same habit (rocky slopes and outcrops). Begonia inumbrata resembles B. fluminensis Brade in the shape of the leaf blades and fruit, and B. pedrabrancencis is morphological similar to B. bidentata Raddi sharing the same shape of the leaf blades and venation. We place both new species in Begonia sect. Pritzelia, based on their similarity to other species in the section, however this section is highly polymorphic, and we highlight that further work is needed on sectional placement. The lectotype of Begonia bidentata Raddi is designated here and we also lectotypified B. ramentacea Paxton using an illustration and designated an epitype.